A Study on Storage Stability of Brown Rice-Based Instant Khichdi Mix - Nishu; Monika Sood; Julie D. Bandral; Neeraj Gupta; Duwa (Archives of Current Research International, 2024)
The objective of the current research was to formulate the instant khichdi mix from processed brown rice (IBR) and dehulled mungbean (IDM) and to evaluate its minerals, bioactive components, microbiological and organoleptic parameters during storage of 90 days. Six composite instant khichdi mixes were formulated by taking different proportions of processed brown rice and dehulled mungbean in the ratios of T1 (100:00::IBR:IDM), T2 (90:10:: IBR:IDM), T3 (80:20::IBR:IDM), T4 (70:30::IBR:IDM), T5 (60:40::IBR:IDM) and T6 (50:50::IBR:IDM). The prepared instant khichdi mix was packed in aluminum laminates and stored under ambient conditions (32 \(±\) 2oC)for a period of 90 days. Results revealed that iron, calcium and potassium showed an increasing trend from 3.53 to 5.50, 26.65 to 67.82 and 256.40 to 700.68 mg per 100 g, respectively with the incorporation of processed dehulled mungbean. The maximum mean total phenolic content of 165.89 mg GAE per 100 g was recorded in treatment T6 (50:50::IBR:IDM). However, the maximum mean antioxidant activity of 46.12 per cent was recorded in treatment T1 (100:00::IBR:IDM). Sensory evaluation revealed that the highest mean overall acceptability scores of 7.91 was recorded in T5 (60:40:: IBR:IDM) which was adjudged as superior among all the treatments of instant khichdi mix. The formulated instant khichdi mix retained its quality throughout the storage period of 90 days with total microbial count within safe limits.